Pre‐training perceived social self‐efficacy accentuates the effects of a cross‐cultural coping orientation program: Evidence from a longitudinal field experiment1. (29th April 2014) - Fan, Jinyan; Lai, Lei
Summary Analyzing additional data from a longitudinal field experiment, the present research investigate whether pre‐training perceived social self‐efficacy (PSSE) may moderate cross‐cultural training effectiveness. On the basis of the interactionist perspective, we hypothesized that sojourners with high pre‐training PSSE would benefit more from a cross‐cultural coping orientation program, called "Realistic Orientation Program for Entry Stress" (ROPES), than sojourners with low pre‐training PSSE. As a result, the treatment effects (the ROPES program over the control program—a traditional cross‐cultural orientation program) would be more positive for high‐PSSE sojourners than for low‐PSSE sojourners. Seventy‐two incoming graduate students from East Asia entering a large US public university were randomly assigned to either a ROPES program or a control program, and were assessed pre‐entry and multiple times post‐entry. The results strongly supported our predictions, as the hypothesized PSSE × Treatment interactions were observed on a comprehensive set of training outcomes based on multisource data. Theoretical and practical implications were discussed. Copyright © 2014 John Wiley & Sons, Ltd.